An Analysis of the Impact of Deposit Rate Ceilings on the Market Values of Thrift Institutions - DANN, LARRY Y.; JAMES, CHRISTOPHER M. (Journal of Finance, 1982)
ABSTRACT This paper examines the impact of changes in deposit interest rate regulations on the common stock values of savings and loan institutions. The analysis indicates that stockholder‐owned savings and loans (S & L's) have experienced statistically significant declines in equity market values at the announcement of the removal of ceilings on certain consumer (small saver) certificate accounts and the introduction of short term variable rate money market certificates. We find the evidence to be consistent with the hypothesis that S & L's have earned economic rents from restrictions on interest rates paid to small saver accounts, and that relaxation of interest rate ceilings has reduced these rents.